Cloud Based Dynamic Workload Management - Mr. K. Chandramohan, Ms. Betsy M Babykutty (International Journal of Scientific Research and Management (IJSRM), 2014)
Dynamic resources allocation system, that uses virtualization technology to allocate data center resources dynamically based on application demands and support green computing by optimizing the number of servers in use. But, this allocation storage had a limits to store a data. The allocation process is very complexity and it needs more server to allocate the resources, so it’s very costly to maintain. To overcome this problem, we proposed, a data compression with the use of j-bit encoding (JBE). This algorithm will manipulates each bit of data inside file to minimize the size without losing any data after decoding which is classified to lossless compression.